The Rockefeller Foundation's "Public Stewardship of Private Providers in Mixed Health Systems": A Point-by-Point Critique - Claudio Schuftan; Jean Pierre Unger (Social Medicine Publication Group, 2024)
The 2010 World Health Assembly (WHA) tabled, but did not manage to discuss, a resolution on regulating the private health care sector. 1  With hindsight, it seems fitting to thoroughly review an earlier 2008 Rockefeller Foundation (RF) report on the same issue: "Public Stewardship of Private Providers in Mixed Health Systems." The key weakness of the RF document - and also of the above WHA draft resolution - is that both fail to provide the necessary empirical evidence to show that better 'stewarding' regulation in low and middle income countries (LMICs) has worked to provide quality, accessible, and affordable health care for all in mixed public-private health systems. In this article, we voice our skepticism about whether public stewardship can work in mixed systems in LMICs. Moreover, the RF report does not address the access to quality health care from a human rights perspective. The right to quality health care is simply overlooked.  The report prescribes "new solutions" to well known regulatory problems and fails to offer any evidence of their benefit. It argues that regulation of mixed public-private health systems can be successful without providing any evidence even at local level. This lack of evidence is striking since we have a good 20 years of experience with such regulation. We conclude that a) private providers will never be effectively controlled in LMICs with regulation alone, and b) that the report reflects RF's ideological bias against single payer, universal coverage public health care systems. We argue that the "regulation alternative" is simply not a substitute for strengthening the public sector. Many of the measures proposed by the Rockefeller Foundation report are not necessarily wrong, but they are applied to a private sector enjoying an established position that has given them access to deliver health care as a privilege and not as a right. Indeed, we remain convinced that if some of the proposed measures were applied to the public health sector with adequate long-term government and donor financing, they would go a longer way to achieve Health Care For All. The past experiences of Costa Rica and Sri Lanka suggest that LMICs private health markets have only effectively been controlled in countries where the public sector was effective in competing with the private sector. A well organized and funded public health system, delivering comprehensive health care (not restricted to vertical disease control programs and not treating health as a commodity) is the only alternative to reign-in the excesses of LMIC private providers in mixed health systems.